VARIASI GAMBAR CADAS DI CERUK LAKANTOBHE DESA LIANGKABORI KECAMATAN LOHIA KABUPATEN MUNA - Putri S Rahmayani; Salniwati Salniwati; Abdul Alim; Arie Toursino Hadi (Laboratorium Jurusan Arkeologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2023)
The Lakantobhe rock-shelter site is one of the rock-shelter that has various rock arts. The site is located in Liangkabori village, Lohia sub-district, Southeast Sulawesi. Muna Regency, Southeast Sulawesi. This research investigated the form of images and variations in the form of rock art in the Lakantobhe rock-shelter site. The method used was data collection, data verifivication, documenting data and then data analysis. The last was data interpretation. The results of the research conducted, the Lakantobhe rock-shelter site has 46 panels with the number of images found, namely 133 images. The findings of these images have different shapes. These forms include human forms with a total of 4 variants, human and animal forms with a total of 4 variants, animal forms with a total of 6 variants, geometric with a total of 7 variants and abstract forms with a total of 35 images.